From Ritual to Theatre in a Northern Manitoba Cree Community - Granzber, Gary (Anthropologica, 2022)
In two later works Victor Turner examines the transition from ritual to theatre. This article, which is based on a case study, elucidates that process. The locale is a Cree community in Northern Manitoba which is undergoing rapid social change. The society's adjustments are examined from the perspective of one individual who plays a key role in the redress phase of the social dramas which begin to dominate daily events as the conflict between traditional and modem systems intensifies. His role is interpreted as being transitional from that which characterizes the ritualized roles of shamans, storytellers and joking partners and that which obtains in the activities of sacred clowns and secular, experimental theatre. It is a self-aware, specialized role in which he uses public storytelling performances to admonish the people not to forget their tradition as they face the future.